(untitled) (BALEAP Journal of Research and Practice, 2025)
This paper discusses a project aimed at integrating social justice into an English for Academic Purposes (EAP) course. Initially conceived as an in-house initiative, the project evolved into a research grant proposal, ultimately enabling a group of hourly-paid pre-sessional teachers to transition from passive recipients of course materials to active participants in the creation and evaluation of course content. The authors emphasise the importance of the teaching-research nexus, as highlighted by McKinley (2019), advocating for practice-based research that reflects real classroom contexts rather than idealised studies. Throughout the project, the teachers gained confidence and developed a stronger connection to mainstream academia, leading to significant professional growth, including one participant securing a permanent university position. The project not only addressed issues of equality, diversity, and inclusivity but also showcased the transformative impact of collaborative research on educators’ careers and their engagement with the academic community.